Transcriptome and Coexpression Network Analyses Reveal Hub Genes in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) During Different Stages of Plasmodiophora brassicae Infection - Yuan, Yuxiang; Qin, Liuyue; Su, Henan; Yang, Shuangjuan; Wei, Xiaochun; Wang, Zhiyong; Zhao, Yanyan; Li, Lin; Liu, Honglei; Tian, Baoming; Zhang, Xiaowei (Frontiers in Plant Science, 2021)
Clubroot, caused by the soil-borne protist Plasmodiophora brassicae, is one of the most destructive diseases of Chinese cabbage worldwide. However, clubroot resistance mechanisms are still unclear. In this study, in both clubroot-resistant (DH40R) and clubroot-susceptible (DH199S) Chinese cabbage lines, the primary (root hair infection) and secondary infection (cortical infection) stages started 2 and 5 days after inoculation (dai), respectively. With the extension of the infection time, cortical infection was blocked and showed complete P. brassica resistance in DH40R; while disease scales of 1, 2 and 3 were observed at 8, 13 and 22 dai in DH199S. Transcriptome analysis at 0, 2, 5, 8, 13 and 22 dai identified 3,851 relative DEGs (rDEGs) between DH40R and DH199S. The results indicated that genes associated with auxin, PR proteins, disease resistance proteins, cell wall biosynthesis and organization, chitinase, oxidative stress, and WRKY and MYB transcription factors were involved in clubroot resistance regulation. In addition, weighted gene coexpression network analysis (WGCNA) identified three of the modules whose functions were highly associated with clubroot-resistant, including 12 hub genes related to clubroot-resistant (MYB44, AGP12, WRKY28, EIL3, ERF060, EXO, NHL13, LOX4, FMO, AOP1, POD56 and COMTL). These results provide valuable information for better understanding the molecular regulatory mechanism of Chinese cabbage clubroot resistance.